RGD‐Conjugated Nanoscale Coordination Polymers for Targeted T1‐ and T2‐weighted Magnetic Resonance Imaging of Tumors in Vivo. (25th October 2013) - Yang, Hong; Qin, Changyuan; Yu, Chao; Lu, Yang; Zhang, Hongwei; Xue, Fengfeng; Wu, Dongmei; Zhou, Zhiguo; Yang, Shiping
<x xml:space="preserve">Abstract</x> Development of multifunctional nanoscale coordination polymers (NCPs) allowing for T1‐ and T2‐weighted targeted magnetic resonance (MR) imaging of tumors could significantly improve the diagnosis accuracy. In this study, nanoscale coordination polymers (NCPs) with a diameter of ≈80 nm are obtained with 1, 1′‐dicarboxyl ferrocene (Fc) as building blocks and magnetic gadolinium(III) ions as metallic nodes using a nanoprecipitation method, then further aminated through silanization. The amine‐functionalized Fc‐Gd@SiO2 NCPs enable the covalent conjugation of a fluorescent rhodamine dye (RBITC) and an arginine‐glycine‐aspartic acid (RGD) peptide as a targeting ligand onto their surface. The formed water‐dispersible Fc‐Gd@SiO2(RBITC)–RGD NCPs exhibit a low cytotoxicity, as confirmed by MTT assay. They have a longitudinal relaxivity (r1) of 5.1 mM−1 s−1 and transversal relaxivity (r2) of 21.7 mM−1 s−1, suggesting their possible use as both T1‐positive and T2‐negative contrast agents. In vivo MR imaging experiments show that the signal of tumor over‐expressing high affinity αvβ3 integrin from T1‐weighted MR imaging is positively enhanced 47±5%, and negatively decreased 33±5% from T2‐weighted MR imaging after intravenous injection of Fc‐Gd@SiO2(RBITC)–RGD NCPs.